First records of the genus Spilopteron Townes (Hymenoptera: Ichneumonidae: Acaenitinae) from Vietnam, with descriptions of five new species - Pham, Nhi Thi; Broad, Gavin R.; Matsumoto, Rikio; Achterberg, Cornelis Van (Zootaxa, 2019)
The genus Spilopteron Townes, 1960 (Ichneumonidae: Acaenitinae) is reported for the first time from Vietnam. Five of the seven reported species are described as new, comprising: S. brunneum sp. nov., S. lamdongensis sp. nov., S. nigromaculatum sp. nov., S. tamdaoensis sp. nov., and S. tumidium sp. nov. In addition, two further species, S. flaviapicus Wang & Huang, 1993, and S. fuscomaculatum Wang, 1988, are recorded for the first time from the country.